1985
DOI: 10.2307/1130169
|View full text |Cite
|
Sign up to set email alerts
|

The Rhythmic Structure of Mother-Infant Interaction in Term and Preterm Infants

Abstract: The purpose of this study was to quantify social interaction rhythms in 3- and 5-month-old term and preterm infants and their mothers. Infant-mother dyads were videotaped in a 3-min face-to-face paradigm. For each second of the interaction, separate scores were assigned to infant and mother indicating levels of affective involvement, creating 2 180-sec time series. Spectral and cross-spectral techniques were used to quantify periodicities in each member of the dyad and to estimate the synchrony or coherence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
158
0
7

Year Published

1989
1989
2010
2010

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 239 publications
(172 citation statements)
references
References 24 publications
6
158
0
7
Order By: Relevance
“…It is logical, therefore, that many researchers have focused their attention on the evolution of parent-child interactions when studying the problems of parenting a low birth weight infant. There have been a large number of interaction studies completed since the late 1970s with an equally large diversity in the methodologies used (e.g., Bakeman ; Barnard, Bee, & Hammond, 1984;Lester, Hoffman, & Brazelton, 1985;Minde, Perrotta, & Hellman, 1987;Mullen, Garcia-Coll, Vohr, Muriel, & Oh, 1988).…”
Section: Parent-infant Interactionmentioning
confidence: 99%
“…It is logical, therefore, that many researchers have focused their attention on the evolution of parent-child interactions when studying the problems of parenting a low birth weight infant. There have been a large number of interaction studies completed since the late 1970s with an equally large diversity in the methodologies used (e.g., Bakeman ; Barnard, Bee, & Hammond, 1984;Lester, Hoffman, & Brazelton, 1985;Minde, Perrotta, & Hellman, 1987;Mullen, Garcia-Coll, Vohr, Muriel, & Oh, 1988).…”
Section: Parent-infant Interactionmentioning
confidence: 99%
“…These data were analyzed using fast Fourier or spectral analysis which is a mathematical way of decomposing and quantifying cycles. The results showed statistically significant rhythms exactly where Brazelton predicted they would be; there were 15 sec cycles in the mother and 15 sec cycles in the baby (Lester, Hoffman, & Brazelton, 1985). This study included term and preterm infants and showed that the cycles were more coordinated in term than in preterm infants.…”
Section: View Of Infant-parent Relationshipmentioning
confidence: 51%
“…The recognition of parents' capacities for nurturance is reinforced by our own microanalytic analyses of early parent-infant interactions (Brazelton, Koslowski, & Main, 1974;Lester, Hoffman, & Brazelton, 1985;Tronick, Als, & Brazelton, 1980). These data demonstrate that the social stimulation provided by caregivers is rich, multimodal, and reciprocal.…”
Section: A Positive-adaptive Modelmentioning
confidence: 86%
“…Although the newborn period often provides the clinician with a unique opportunity to develop a relationship with the infant's father (Beal, 1984;Myers, 1982), the effectiveness of the NBAS session can benefit from the inclusion of the siblings, grandparents, or other important elements of the infant's social network, because they all need to adjust to the presence of the new family member (Minuchin, 1985). Expanding the scope of the intervention to include a broader range of potentially supportive allies is particularly important when working with families under stress, such as economically disadvantaged families, single-parent families, adolescent parents, families with premature or SGA infants, or families with infants who are behaviorally irritable and difficult to handle (e.g., Crockenberg, 1981 ;Field, 1987;Garbarino, 1982;Lester, Hoffman, & Brazelton, 1985;Parke & Tinsley, 1982;Zigler & Frank, 1988). In this way we use the NBAS intervention to try to bridge the gap between the famliy and support networks within the community.…”
Section: The Newborn As Part Of a Social Networkmentioning
confidence: 99%